How children experience their kindergarten - Zjačić-Ljubičić, Sandra; Očko, Lana (Rethinking childhood II: child and space, 2026)
By providing the child with the opportunity to actively participate in the planning of activities in which they participate, we respect said child’s right to continuity in upbringing and education. By introducing the child into the process, we give him the opportunity to choose what suits him. By following his needs and interests, we achieve one of our goals, which includes improving and changing the educational approach. In this paper, special emphasis is placed on the experience that children have in connection with the activity centres in the living room and the sports hall. The aim of this work is to show children’s experiences of activity centres and gymnasiums by asking questions to children aged six to seven years, and by having the children record and photograph the centres and the gymnasium themselves. Another aim was to encourage children’s initiative and self-organisation in the design of activity centres, as well as the creation of their own activities in them. Children should be encouraged to express proposals, initiatives and suggestions that are taken into account when it comes to shaping the educational process, which also encourages the development of the child’s civic competences. In this way, children become trained for democratic dialogue with other participants in the process and prepared for active participation in the life and work of the social community. In our work, we used the Mosaic approach. We try to answer the questions of what children like to do, and what their favourite place in kindergarten tends to be. Based on the obtained results, we can conclude that children of early and preschool age prefer to express what they like, rather than what they don’t like. The favourite places that children photographed and filmed were those that facilitated children’s initiative, encouraged imagination and physical activity. Children chose places and environments that supported different types of communication. Symbolic play in the most advanced way encouraged the development of metacognitive abilities and a sense of self-satisfaction in children. In contrast, children remained reluctant to choose centres where they had to sit for extended periods.